Slow Learners’ Difficulties in Learning Basic English Literacy and Numeracy at SMP L Sidoharjo - Oktaviani, Ayu; Yulfi, Yulfi; Episiasi, Episiasi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research was obtained to investigate slow learners’ difficulties in learning Basic English literacy and numeracy at SMP N L Sidoharjo Musi Rawas Distric. Mix method was be applied in conducting this research in order to answer two research questions about the slow learners’ difficulties and the factors of difficulties in learning Basic English literacy and numeracy. In collecting data, the researchers used diagnostic test and interview. Twenty seventh grader slow learners’took part as the subject of the research. And data from test were analyzed quantitatively, while data from interview were analyzed qualitatively by using model analysis of Miles and Huberman: data collection, condensation, data display and drawing and verifying conclusion. After analyzing data, it was found that slow learners at SMP L Sidoharjo face difficulties in Basic English Literacy and Numeracy. In literacy, they have problem in reading, especially in getting specific information from the text. Then, they also faced difficulties in arranging words into simple sentences and arranging simple sentences into a good paragraph. While in numeracy, they were difficult in comprehending data in the form of table, graph or chart. Calculating how much they have paid (price) and writing number into words became other difficulties for them. These difficulties were caused by several factors that come from internal and external factors. Their cognitive intelligence and their attitude in learning English were factors from themselves. In addition, their parents’ careless relating to their study, limitation of learning facilities and their parents’ educational background were affected to their success in learning. Furthermore, the quantity of using learning media and unvaried teaching techniques used by the English teacher affected to their interest and enthusiastic in learning English. These all became the factors of their difficulties in learning Basic English Literacy and Numeracy. Keywords: Basic English, Learning Difficulties, Literacy, Numeracy, Slow Learners